Mapping intangibilities in creative tourism territories through tangible objects: a methodological approach for developing creative tourism offers - Cabeça, Sónia Moreira (2019)
What can people express about their places through the objects that they valorise and link to their territory? Can objects create narratives about a place's identity and collect significant cultural information that locate people in their places? Can such cultural mapping be a useful tool in the design of creative tourist offers? The Project CREATOUR held a series of Idea Laboratories with several entities that provide creative tourism experiences, approaching cultural mapping through objects as a tool for regional actors to discover what is 'so special' about their places, a way to link tourism offers with the community where they take place. These exercise lead participants to remark on the importance and idiosyncrasy of their regions and evidenced the importance of cultural mapping to a more sustainable offer and the overall marketing of destinations. Mapping intangibilities through tangible objects helped to capture what gives meaning to particular places.